On the relationship between mobility, population growth, and capital spending in the United States - Marco Bassetto; Leslie McGranahan (Federal Reserve Bank of Chicago, 2009)
In this paper, we assess the empirical relationship between population growth, mobility, and state-level capital spending in the United States. To evaluate the magnitude of the coefficients, we introduce an explicit, quantitative political-economy model of government spending determination, where mobility and population growth generate departures from Ricardian equivalence. Our estimates find strong responses in the level of capital provision per capita to these demographic movements; in fact, the resulting coefficients are stronger than the model delivers. Regression coefficients on population growth and mobility also yield opposite implications for the direction to which spending is distorted by the politicaleconomy friction, posing a further challenge.
Keywords: 330